Acoustic changes in the speech of children with cerebral palsy following an intensive program of dysarthria therapy*. Issue 1 (17th July 2017) - Pennington, Lindsay; Lombardo, Eftychia; Steen, Nick; Miller, Nick
Abstract: Background: The speech intelligibility of children with dysarthria and cerebral palsy has been observed to increase following therapy focusing on respiration and phonation. Aims: To determine if speech intelligibility change following intervention is associated with change in acoustic measures of voice. Methods & Procedures: We recorded 16 young people with cerebral palsy and dysarthria (nine girls; mean age 14 years, SD = 2; nine spastic type, two dyskinetic, four mixed; one Worster–Drought) producing speech in two conditions (single words, connected speech) twice before and twice after therapy focusing on respiration, phonation and rate. In both single‐word and connected speech we measured vocal intensity (root mean square—RMS), period‐to‐period variability (Shimmer APQ, Jitter RAP and PPQ) and harmonics‐to‐noise ratio (HNR). In connected speech we also measured mean fundamental frequency, utterance duration in seconds and speech and articulation rate (syllables/s with and without pauses respectively). All acoustic measures were made using Praat. Intelligibility was calculated in previous research. Outcomes & Results: In single words statistically significant but very small reductions were observed in period‐to‐period variability following therapy: Shimmer APQ –0.15 (95% CI = –0.21 to –0.09); Jitter RAP –0.08 (95% CI = –0.14 to –0.01); Jitter PPQ –0.08 (95% CI = –0.15 to –0.01). No changes in period‐to‐period perturbation across phrases in connected speech were detected. However, changes in connected speech were observed in phrase length, rate and intensity. Following therapy, mean utterance duration increased by 1.11 s (95% CI = 0.37–1.86) when measured with pauses and by 1.13 s (95% CI = 0.40–1.85) when measured without pauses. Articulation rate increased by 0.07 syllables/s (95% CI = 0.02–0.13); speech rate increased by 0.06 syllables/s (95% CI = < 0.01–0.12); and intensity increased by 0.03 Pascals (95% CI = 0.02–0.04). There was a gradual reduction in mean fundamental frequency across all time points (–11.85 Hz, 95% CI = –19.84 to –3.86). Only increases in the intensity of single words (0.37 Pascals, 95% CI = 0.10–0.65) and reductions in fundamental frequency (–0.11 Hz, 95% CI = –0.21 to –0.02) in connected speech were associated with gains in intelligibility. Conclusions & Implications: Mean reductions in impairment in vocal function following therapy observed were small and most are unlikely to be clinically significant. Changes in vocal control did not explain improved intelligibility. Abstract : Video Abstract .